Efficient preparation method of rhenium-containing alloy with small grain size

Through solution combustion method and four-stage heating and heating reduction technology, combined with hydraulic press pressing and two-step sintering treatment, the problem of efficient utilization and uniform distribution of rhenium elements in alloy materials is solved, and high-performance, corrosion-resistant nano alloy materials are prepared.

CN120138407APending Publication Date: 2025-06-13FUZHOU UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510355865.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-25
Publication Date
2025-06-13

AI Technical Summary

Technical Problem

When preparing high-performance rhenium alloy materials, how to achieve efficient utilization, uniform distribution and reduced dosage of rhenium elements, which not only meets high-performance requirements but also is economical, especially in the field of extreme environmental applications.

Method used

The nanoalloy powder precursor was prepared by solution combustion method, and the nanoalloy powder was obtained by four-stage heating and heating reduction, and was pressed and molded by a hydraulic press, and finally, a two-step sintering treatment was carried out in a hydrogen or an inert gas environment.

Benefits of technology

The efficient utilization and uniform distribution of rhenium elements were achieved, and nano alloy materials with high purity, uniform doping, excellent mechanical properties, corrosion resistance and long life were prepared.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120138407A_ABST
    Figure CN120138407A_ABST
Patent Text Reader

Abstract

The invention discloses an efficient preparation method of a small-grain-size rhenium-containing alloy, and relates to the technical field of refractory metal powder metallurgy. The preparation method mainly comprises the following steps: preparing oxide composite powder by adopting a combustion synthesis method and taking soluble transition metal salt, ammonium perrhenate, hydrogen peroxide or ammonium nitrate and fuel as raw materials, reducing the oxide composite powder through hydrogen to obtain nano alloy powder, and performing compression molding and high-temperature sintering through a hydraulic press to prepare the rhenium-containing alloy material. The material has the advantages of being high in purity, uniform in doping, excellent in mechanical performance, resistant to corrosion, long in service life and the like, and a new breakthrough is brought to the field of powder metallurgy of refractory metal.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of powder metallurgy and relates to a method for preparing a high-efficiency rhenium-containing alloy with small grain size. Background Art

[0002] With the rapid development of modern industrial technology, the requirements for material properties are constantly rising. Especially in the application fields under extreme conditions such as aerospace and nuclear industry, the radiation resistance and corrosion resistance of materials have become the key indicators to measure their applicability. These harsh application environments have given rise to an urgent need for innovative and high-performance alloy materials.

[0003] Rhenium, as a rare refractory metal, has attracted much attention due to its unique physical and chemical properties. It has an extremely high melting point, excellent mechanical properties, and stable performance under extreme conditions, making rhenium play an indispensable role in the fields of aerospace and electronics industry (Hong Tao, Jiao Pengli, Wu Qi, etc. "The Difficult-to-Obtain Aerospace Metal 'Rhenium'" [J]. Bulletin of Mineralogy, Petrology and Geochemistry, 2023, 42(03): 680 - 684). More importantly, rhenium exhibits excellent corrosion resistance and radiation resistance, establishing its position as a preferred element for preparing high-performance alloy materials (Li Jing, Yan Feng, Zuo Yufei, etc. Rhenium Resources, Market and Technology Progress [J]. China Molybdenum Industry, 2023, 47(02): 8 - 15).

[0004] However, despite the many advantages of rhenium, its scarcity and high cost also pose serious challenges. While ensuring the alloy properties, how to reduce the amount of rhenium used and improve its utilization efficiency has become a difficult problem that scientific researchers urgently need to solve. In addition, how to achieve uniform distribution of rhenium element in the alloy, reduce the oxygen content and improve the material density during the preparation process are also the key problems faced by the modern powder metallurgy field.

[0005] To address these challenges, researchers are constantly exploring new preparation methods and processes, and are committed to developing a rhenium-containing alloy material that can not only meet the high-performance requirements but also be economical. This new material should not only have excellent radiation resistance and corrosion resistance, but also achieve efficient utilization and uniform distribution of rhenium element during the preparation process. This will provide a more reliable and durable material solution for the application fields under extreme conditions such as aerospace and nuclear industry, and thus promote the technological innovation and industrial development of related fields. Summary of the Invention

[0006] The object of the present invention is to propose a new method for preparing a high-efficiency rhenium-containing alloy with small grain size in view of the above problems. This method prepares a nano-alloy powder precursor by solution combustion method, then obtains the nano-alloy powder through four-stage heating and reduction, and then uses a hydraulic press to press it into a blank, and finally obtains the alloy material through steps such as two-step sintering. This material has the advantages of high purity, uniform doping, excellent mechanical properties, corrosion resistance and long service life, bringing new breakthroughs to the field of refractory metal powder metallurgy.

[0007] To achieve the above object, the present invention adopts the following technical solutions: A method for preparing a high-efficiency rhenium-containing alloy with small grain size, wherein the rhenium-containing alloy is composed of the following components by mass fraction: 70 wt% - 99 wt% of one or more transition metal elements, and 1 wt% - 30 wt% of rhenium, and the rest are unavoidable impurities. The preparation method includes the following steps: Step 1, preparing a nano-alloy powder precursor by solution combustion method. The specific process is to dissolve a certain proportion of soluble transition metal salts, ammonium perrhenate, hydrogen peroxide or ammonium nitrate, and fuel in water to form an aqueous solution, and then heat the solution to initiate a combustion reaction to obtain the precursor powder; Step 2, reducing the obtained precursor powder by a four-stage heating and temperature-raising method in a hydrogen environment to obtain a nano-alloy powder; Step 3, pressing the nano-alloy powder into a shape and treating it by a two-step sintering method in a hydrogen or inert gas environment.

[0008] Preferably, in step 1, the fuel is at least one of glycine, glucose, sucrose, and fructose.

[0009] Preferably, in step 1, the molar ratio of the soluble transition metal salt, ammonium perrhenate, hydrogen peroxide or ammonium nitrate, and fuel is 1: (0.01 - 0.5): (5 - 100): (5 - 100).

[0010] Preferably, in step 1, the heating range of the solution is 150 - 300 °C.

[0011] Preferably, the four-stage heating and temperature-raising method in step 2 includes the following steps: First, heat from room temperature to 100 - 200 °C at a heating rate of 1 - 10 °C / min and hold for 0.5 - 10 h; Then continue to heat to 200 - 400 °C at a heating rate of 1 - 10 °C / min and hold for 0.5 - 10 h; Then continue to heat to 400 - 600 °C at a heating rate of 1 - 10 °C / min and hold for 0.5 - 10 h; Finally, continue to heat to 600 - 800 °C at a heating rate of 1 - 10 °C / min and hold for 0.5 - 10 h.

[0012] Preferably, during the reduction process in step 2, hydrogen is continuously introduced with a flow rate of 0.1 - 1 L / min.

[0013] Preferably, in step 3, a hydraulic press is used for the pressing operation with a pressing pressure of 500 MPa - 800 MPa and a pressure holding time of 1 - 10 min.

[0014] Preferably, the two-step sintering method in step 3 specifically includes the following steps: Heat from room temperature to 1200 - 1500 °C at a heating rate of 1 - 10 °C / min and hold for 0.5 - 10 h; Then cool down by 50 - 150 °C at a cooling rate of 1 - 10 °C / min and hold for 0.5 - 10 h.

[0015] Preferably, during the sintering process in step 3, hydrogen or an inert gas needs to be continuously introduced with a flow rate of 0.1 - 1 L / min.

[0016] Preferably, the transition metal elements include tungsten, molybdenum, and zirconium.

[0017] The present invention has the following advantages: ① The solution combustion method in the wet chemical method is used to prepare the precursor. This method can ensure the molecular-level uniform mixing of different components in the solution state, thereby obtaining precursor powder with a uniform distribution of internal metal oxides.

[0018] ② The four-stage temperature-rising hydrogen reduction method is used to prepare the alloy powder, which not only has a short reduction time and low energy consumption, but also the prepared alloy powder has the characteristics of high purity, fine particle size, and uniform doping.

[0019] ③ The application of the two-step sintering method effectively controls the grain growth and avoids the negative impact of grain coarsening on the material properties. Description of the Drawings

[0020] Figure 1 is the process flow chart of the present invention; Figure 2 is the SEM image of the tungsten-rhenium alloy sample prepared in Example 1 of the present invention. Detailed Embodiments

[0021] A method for preparing a high-efficiency rhenium-containing alloy with small grain size, wherein the rhenium-containing alloy is composed of the following components by mass fraction: 70 wt% - 99 wt% of one or more transition metal elements, and 1 wt% - 30 wt% of rhenium, and the rest are unavoidable impurities. The preparation method includes the following steps: Step 1: Mix soluble transition metal salts, ammonium perrhenate, hydrogen peroxide or ammonium nitrate, and fuel in a specific molar ratio in water to form an aqueous solution, and prepare precursor powder by heating to initiate a combustion reaction; Step 2: Place the obtained precursor powder in a hydrogen atmosphere and reduce it by a four-stage heating and temperature-rising method to obtain nano-alloy powder. The heating and temperature-rising need to follow a specific procedure; Step 3: Press the nano-alloy powder into shape with a hydraulic press, and place the pressed green body in a hydrogen or inert gas environment and treat it by a two-step sintering method.

[0022] Further, the fuel in Step 1 is at least one of glycine, glucose, sucrose, and fructose.

[0023] Further, the molar ratio of the soluble transition metal salt, ammonium perrhenate, hydrogen peroxide or ammonium nitrate, and fuel in Step 1 is 1: (0.01 - 0.5): (5 - 100): (5 - 100).

[0024] Further, the heating range of the solution in Step 1 is 150 - 300 °C.

[0025] Further, the four-stage heating and temperature-rising method in Step 2 includes the following steps: ① Heat from room temperature to 100 - 200 °C, with a heating rate of 1 - 10 °C / min, and keep warm for 0.5 - 10 h; ② Continue to heat to 200 - 400 °C, with a heating rate of 1 - 10 °C / min, and keep warm for 0.5 - 10 h; ③ Continue to heat to 400 - 600 °C, with a heating rate of 1 - 10 °C / min, and keep warm for 0.5 - 10 h; ④ Continue to heat to 600 - 800 °C, with a heating rate of 1 - 10 °C / min, and keep warm for 0.5 - 10 h.

[0026] Further, during the reduction process in Step 2, hydrogen needs to be continuously introduced, and the flow rate is 0.1 - 1 L / min.

[0027] Further, the pressing pressure in Step 3 is 500 MPa - 800 MPa, and the pressure holding time is 1 - 10 min.

[0028] Further, the two-step sintering method described in step 3 includes the following steps: ① Heat from room temperature to 1200 - 1500 °C at a heating rate of 1 - 10 °C / min and hold for 0.5 - 10 h.

[0029] ② Cool down by 50 - 150 °C at a cooling rate of 1 - 10 °C / min and hold for 0.5 - 10 h.

[0030] Further, during the sintering process described in step 3, it is necessary to keep hydrogen or inert gas flowing in, and the flow rate is 0.1 - 1 L / min.

[0031] Example 1 Add 0.0097 mol of ammonium tungstate, 0.0036 mol of ammonium perrhenate, 0.9 mol of ammonium nitrate and 0.9 mol of glycine into a 2 L beaker, and add 200 mL of water to dissolve to obtain a clear solution. Then, heat it to 150 °C to cause a solution combustion reaction to obtain a fluffy precursor powder. Carry out reduction treatment of the precursor powder in a tubular furnace, where the hydrogen flow rate is 1 L / min, the heating rate is 10 °C / min, and keep warm according to the following temperature sequence: ① Keep warm at 100 °C for 10 h; ② Keep warm at 200 °C for 10 h; ③ Keep warm at 400 °C for 10 h; ④ Keep warm at 600 °C for 10 h. Subsequently, use a hydraulic press to press the obtained nano-alloy powder into a blank, the pressing pressure is 500 MPa, and the pressure holding time is 10 min. Finally, carry out sintering treatment in a tubular furnace: in the first stage, heat to 1500 °C at a heating rate of 5 °C / min, hold for 0.5 h, and the hydrogen flow rate is 1 L / min; in the second stage, cool to 1350 °C at a cooling rate of 5 °C / min, hold for 0.5 h, and the hydrogen flow rate is 1 L / min.

[0032] The relative density of the obtained tungsten rhenium alloy sample is 99.3%, the average grain size is 780 nm, and the SEM image is shown in the appendix Figure 2 .

[0033] Example 2 0.12 mol of ammonium molybdate, 0.0012 mol of ammonium perrhenate, 0.6 mol of ammonium nitrate and 0.6 mol of sucrose were added to a 2 L beaker, and 400 mL of water was added to dissolve them to obtain a clear solution. Then, it was heated to 250 °C until a solution combustion reaction occurred to obtain a fluffy precursor powder. The precursor powder was subjected to reduction treatment in a tubular furnace, where the hydrogen flow rate was 0.1 L / min, the heating rate was 10 °C / min, and heat preservation was carried out according to the following temperature sequence: ① Heat preservation at 200 °C for 1 h; ② Heat preservation at 400 °C for 1 h; ③ Heat preservation at 600 °C for 1 h; ④ Heat preservation at 800 °C for 1 h. Subsequently, the obtained nano-alloy powder was pressed into a blank using a hydraulic press, the pressing pressure was 750 MPa, and the pressure holding time was 5 min. Finally, sintering treatment was carried out in a tubular furnace: in the first stage, it was heated to 1350 °C, the heating rate was 10 °C / min, heat preservation was carried out for 1 h, and the hydrogen flow rate was 0.5 L / min; in the second stage, it was cooled to 1300 °C, the cooling rate was 10 °C / min, heat preservation was carried out for 5 h, and the hydrogen flow rate was 0.5 L / min.

[0034] The obtained molybdenum-rhenium alloy sample had a relative density of 99.6% and an average grain size of 940 nm.

[0035] Example 3 0.08 mol of zirconium nitrate, 0.04 mol of ammonium perrhenate, 0.4 mol of hydrogen peroxide, 0.2 mo of glucose and 0.2 mol of fructose were added to a 2 L beaker, and 150 mL of water was added to dissolve them to obtain a clear solution. Then, it was heated to 300 °C until a solution combustion reaction occurred to obtain a fluffy precursor powder. The precursor powder was subjected to reduction treatment in a tubular furnace, the hydrogen flow rate was 0.3 L / min, the heating rate was 10 °C / min, and heat preservation was carried out according to the following temperature sequence: ① Heat preservation at 150 °C for 3 h; ② Heat preservation at 250 °C for 3 h; ③ Heat preservation at 450 °C for 3 h; ④ Heat preservation at 650 °C for 3 h. Subsequently, the obtained nano-alloy powder was pressed into a blank using a hydraulic press, the pressing pressure was 800 MPa, and the pressure holding time was 1 min. Finally, sintering treatment was carried out in a tubular furnace: in the first stage, it was heated to 1200 °C, the heating rate was 1 °C / min, heat preservation was carried out for 10 h, and the argon flow rate was 0.3 L / min; in the second stage, it was cooled to 1050 °C, the heating rate was 1 °C / min, heat preservation was carried out for 10 h, and the argon flow rate was 0.1 L / min.

[0036] The obtained zirconium-rhenium alloy sample had a relative density of 98.3% and an average grain size of 640 nm.

[0037] Comparative Example 1 Put 0.1164 mol of tungsten powder and 0.0036 mol of rhenium powder into a ball mill and ball mill for 12 h under sealed conditions. Then use a hydraulic press to press the obtained nano-alloy powder into a blank, with a pressing pressure of 500 MPa and a pressure holding time of 10 min. Finally, carry out sintering treatment in a tube furnace: heat to 1500 °C in the first stage, with a heating rate of 5 °C / min, hold for 0.5 h, and the hydrogen flow rate is 1 L / min; in the second stage, cool to 1350 °C, with a cooling rate of 5 °C / min, hold for 0.5 h, and the hydrogen flow rate is 1 L / min.

[0038] Comparative Example 2 Add 0.08 mol of ammonium molybdate, 0.04 mol of ammonium perrhenate, 0.4 mol of hydrogen peroxide, 0.2 mol of glucose and 0.2 mol of fructose into a 2 L beaker, and add 150 mL of water to dissolve to obtain a clear solution. Then, heat to 300 °C until a solution combustion reaction occurs to obtain a fluffy precursor powder. Carry out reduction treatment of the precursor powder in a tube furnace, with a hydrogen flow rate of 0.3 L / min and a heating rate of 10 °C / min, and hold at the following temperature sequence: ① hold at 200 °C for 2 h; ② hold at 900 °C for 4 h; finally, carry out sintering treatment in a tube furnace: heat to 1500 °C, with a heating rate of 10 °C / min, hold for 10 h, and the hydrogen flow rate is 1 L / min.

[0039] Comparative Example 3 Put 0.08 mol of zirconium powder and 0.04 mol of rhenium powder into a ball mill and ball mill for 12 h under sealed conditions. Then use a hydraulic press to press the obtained nano-alloy powder into a blank, with a pressing pressure of 800 MPa and a pressure holding time of 1 min. Finally, carry out sintering treatment in a tube furnace: heat to 1500 °C, with a heating rate of 10 °C / min, hold for 10 h, and the hydrogen flow rate is 1 L / min.

[0040] Table 1. Comparison of alloy properties prepared by different methods *Corrosion weight loss experiment: Immerse the alloy sheet in a physiological saline solution for 7 days and measure the mass change of the alloy sheet before and after.

[0041] The solution combustion method, the four-stage hydrogen reduction method and the two-step sintering method can obtain alloy materials with smaller average particle sizes, making them have higher hardness and stronger corrosion resistance.

[0042] The above are only the preferred embodiments of the present invention, and all equivalent changes and modifications made according to the scope of the patent application of the present invention shall fall within the scope of the present invention.

Claims

1. A method for preparing an efficient small grain size rhenium-containing alloy, characterized in that: The rhenium-containing alloy is composed of the following components by mass fraction: 70 wt% to 99 wt% of one or more transition metal elements, and 1 wt% to 30 wt% of rhenium, and the rest are unavoidable impurities. The preparation method comprises the following steps: Step 1, preparing a nano alloy powder precursor by solution combustion method, the specific process is to dissolve a certain proportion of soluble transition metal salt, ammonium perrhenate, hydrogen peroxide or ammonium nitrate, and fuel in water to prepare an aqueous solution, and then heat the solution to induce a combustion reaction to obtain a precursor powder; Step 2, in a hydrogen environment, reducing the obtained precursor powder by a four-stage heating method to prepare a nano alloy powder; Step 3, pressing the nano alloy powder into a shape, and treating it by a two-step sintering method in a hydrogen or inert gas environment.

2. The method according to claim 1, characterized in that: In step 1, the fuel is at least one of glycine, glucose, sucrose and fructose.

3. The method according to claim 1, characterized in that In step 1, the molar ratio of the soluble transition metal salt, ammonium perrhenate, hydrogen peroxide or ammonium nitrate, and the fuel is 1: (0.01 to 0.5): (5 to 100): (5 to 100).

4. The method according to claim 1, characterized in that The solution heating range in step 1 is 150 ~ 300 °C.

5. The method according to claim 1, characterized in that: The four-stage heating method in step 2 comprises the following steps: First, heat the room temperature to 100 ~ 200 ℃, with a heating rate of 1 ~ 10 ℃ / min, and keep warm for 0.5 ~ 10 h; Then continue heating to 200 ~ 400 ℃, with a heating rate of 1 ~ 10 ℃ / min, and keep warm for 0.5 ~ 10 h; Then continue heating to 400 ~ 600 ℃, with a heating rate of 1 ~ 10 ℃ / min, and keep warm for 0.5 ~ 10 h; Finally, continue heating to 600 ~ 800 ℃ with a heating rate of 1 ~ 10 ℃ / min and keep warm for 0.5 ~ 10 h.

6. The method according to claim 1, characterized in that During the reduction process in step 2, hydrogen is kept flowing at a flow rate of 0.1 to 1 L / min.

7. The method according to claim 1, characterized in that In step 3, a hydraulic press is used for compression molding, the compression pressure is 500 MPa to 800 MPa, and the holding time is 1 to 10 min.

8. The method according to claim 1, characterized in that The two-step sintering method in step 3 specifically includes the following steps: Heat from room temperature to 1200 ~ 1500 ℃ at a heating rate of 1 ~ 10 ℃ / min and keep warm for 0.5 ~ 10 h; Then cool down from 50 to 150 °C at a rate of 1 to 10 °C / min and keep warm for 0.5 to 10 h.

9. The method according to claim 1, characterized in that: During the sintering process in step 3, hydrogen or inert gas needs to be continuously introduced at a flow rate of 0.1 to 1 L / min.

10. The method according to claim 1, characterized in that Transition metal elements include tungsten, molybdenum and zirconium.

Citation Information

Cited By

  • Preparation method of second-phase reinforced tungsten-rhenium alloy

    CN120480211A